The effect of storage to optical properties in case of two apple fruit varieties - El Shal, A. M.; Riczu, P.; Nagy, A.; Sulyok, E.; Szabó, Z.; Nyéki, J. (International Journal of Horticultural Science, 2016)
The keeping quality of fruits is a very important factor in storage point of view, since it could be elongated the consumption time of fruits. In many cases the storage may be necessary, e.g. in short time it is not able to market due to the rich harvest, or all fruits could sell in markets throughout the year. The keeping quality of various fruit species is greatly different; moreover it could be observed some differences between the varieties as well. In our research, we have investigated the spectral properties of the external surface and fl esh of two ripe apple varieties – Jonagored and Granny Smith – before and after storage (about 3°C and about three weeks). The hyperspectral investigation was carried out with AvaSpec-2048 Fiber Optic Spectrometer. The experimental results represented the differences between healthy and chilling injured apple fruits. Furthermore, some indices were created to given countenance to the spectral differences.